The Role of Parents in Early Childhood Character Development in RA Tgk in Panteue Pidie Jaya Regency - Asrida; Abdullah, Nazaruddin; Ismail, Nazaruddin (PT. Anagata Sembagi Education, 2025)
Early childhood character development is a crucial aspect of their personality growth. This study aims to analyze the role of parents in shaping children's character at RA Tgk Di Panteue, Pidie Jaya Regency. The research employs a qualitative approach with observations, interviews, and questionnaires to collect data from parents of students. The findings indicate that parents play a significant role in character formation through positive role modeling, the application of moral and religious values, and the creation of a safe and loving environment. They teach values such as honesty, responsibility, empathy, and mutual respect through daily activities such as performing religious rituals together, speaking politely, and maintaining cleanliness. Based on questionnaire analysis, the level of parental participation in character development reached 82.9%, demonstrating active involvement in the process. However, several challenges hinder character development, including inconsistency in implementing values at home and school, as well as differences in parenting methods within families. Additionally, social environmental influences pose a challenge in maintaining the values taught. Despite these challenges, parents continue to provide the best guidance to ensure that children grow with strong and confident character. This study emphasizes that active parental involvement is essential in establishing a solid foundation for children's character development from an early age.